Antibody therapy of cancer - Scott, Andrew M.; Wolchok, Jedd D.; Old, Lloyd J. (Nature reviews. Cancer, 2012)
Key Points Antibody-based therapy for cancer has become established over the past 15 years and is now one of the most successful and important strategies for treating patients with haematological malignancies and solid tumours. Evidence from clinical trials of antibodies in cancer patients has revealed the importance of iterative approaches for the selection of antigen targets and optimal antibodies. The killing of tumour cells using monoclonal antibodies (mAbs) can result from direct action of the antibody (through receptor blockade, for example), immune-mediated cell killing mechanisms, payload delivery, and specific effects of an antibody on the tumour vasculature and stroma. Tumour antigens that have been successfully targeted include epidermal growth factor receptor (EGFR), ERBB2, vascular endothelial growth factor (VEGF), cytotoxic T lymphocyte-associated antigen 4 (CTLA4), CD20, CD30 and CD52. Serological, genomic, proteomic and bioinformatic databases have also been used to identify antigens and receptors that are overexpressed in tumour cell populations or that are linked to gene mutations identified as driving cancer cell proliferation, including EGFRvIII, MET, CTLA4 and fibroblast activation protein (FAP). The successful development of candidate mAbs for the clinic involves a complex process of scientific and preclinical evaluations that include identification of the physical and chemical properties of the antibody; the detailed specificity analysis of antigen expression; the study of the immune effector functions and signalling pathway effects of the antibody; the analysis of in vivo antibody localization and distribution in transplanted or syngeneic tumour systems; and the observation of the in vivo therapeutic activity of the antibody. A major objective for the clinical evaluation of mAbs has been determining the toxicity and therapeutic efficacy of the antibody alone or as a delivery system for radioisotopes or other toxic agents. It is also crucial to assess its in vivo specificity by determining its biodistribution in patients and to assess the ratio of antibody uptake in the tumour versus normal tissues. Twelve antibodies have received approval from the US Food and Drug Administration for the treatment of various solid tumours and haematological malignancies, and a large number of additional therapeutic antibodies are currently being tested in early stage and late-stage clinical trials. The development of therapeutic antibodies requires a substantial understanding of cancer serology, protein-engineering techniques, mechanisms of action and resistance, and the interplay between the immune system and cancer cells. This Review outlines the fundamental strategies required to develop antibody therapies for cancer patients. The use of monoclonal antibodies (mAbs) for cancer therapy has achieved considerable success in recent years. Antibody–drug conjugates are powerful new treatment options for lymphomas and solid tumours, and immunomodulatory antibodies have also recently achieved remarkable clinical success. The development of therapeutic antibodies requires a deep understanding of cancer serology, protein-engineering techniques, mechanisms of action and resistance, and the interplay between the immune system and cancer cells. This Review outlines the fundamental strategies that are required to develop antibody therapies for cancer patients through iterative approaches to target and antibody selection, extending from preclinical studies to human trials.